Pengaruh Sertifikasi Guru terhadap Kinerja Guru di MTs Negeri Model Makassar - Muhammad Rizal Hamzah; Muzakkir; Mardhiah; Lisnasari Andi Mattoliang; Ahmad Farham Majid (Al Asma: Journal of Islamic Education, 2023)
This study aimed to determine teacher certification's effect on teacher performance at MTs Negeri Model Makassar. This research is a type of quantitative research with an ex-post facto approach. The study population consisted of all 70 certified teachers at MTs Negeri Model Makassar, with a total sample of 25 teachers. The instruments used by researchers in this study were documentation and scales as primary instruments and interview guidelines as secondary instruments. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. Based on the results of the study, it shows that the relationship between teacher certification and teacher performance is in the moderate category. Thus, it was concluded that there was an influence between teacher certification on performance at MTs Negeri Model Makassar.